Emergency toe-to-hand transfer for post-traumatic finger reconstruction: A multicenter case series. (December 2019) - Georgescu, Alexandru Valentin; Battiston, Bruno; Matei, Ileana Rodica; Soucacos, Panayotis N.; Bumbasirevic, Marko; Toia, Francesca; Tos, Pierluigi
Abstract: Background: The aim of this paper was to evaluate the outcomes of a homogenous series of emergency with a toe-to-hand transfer reconstructions with a different timing: immediate (same surgical step with the debridement), primary (in the first 24 h), early (24–72 h after the debridement) or delayed (72 h-7 days). Materials and methods: Between 2001 and 2011, 31 patients received an immediate reconstruction with a toe-to-hand transfer. Data on indications, timing, type of surgery, complications and outcomes (sensory and motor recovery, patient satisfaction) were extrapolated and recorded. Results: Most of the procedures in our series (71%) were performed in the first 24 h. Survival rate was 100%. The only complications were 3 venous thrombosis (10%), solved with surgical re-exploration. Only 1 patient required secondary surgery for web deepening. No functional problems were recorded at the donor site. Sensibility recovery was acceptable in all patients; toe mobility was higher for the reconstructed thumb (85%) than for other digits (77%). Patient satisfaction was high with regard to functional results and lower but acceptable with regard to the aesthetic outcome. There was no difference in satisfaction rate of patients treated within 24 h or within 7 days. Conclusion: No conclusive evidence exists in favor of an immediate versus a primary, early or delayed emergency reconstruction. Emergency toe transfer for finger reconstruction is a safe procedure and its outcomes are comparable to those reported in the literature for secondary reconstruction. Immediate reconstruction has the advantage of an easier dissection, but early or delayed reconstruction gives more time to discuss with the patient and to plan surgery.